2002
DOI: 10.1094/cchem.2002.79.4.572
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Storage Temperature and Kernel Physical Condition on Popping Qualities of Popcorn Hybrids

Abstract: Effect of storage temperature before popping and kernel physical properties on popping characteristics were studied using popcorn (Zea mays L.) hybrids harvested in 1997. Popped volume (PV), unpopped kernel ratio (UPK), and popping times were measured from 250 g of moisture‐adjusted kernels stored at 30, 1, and −29°C for one month. Maximum popped volume (MPV) and minimum unpopped kernel ratio (MUPK) at the corresponding optimum moisture contents (OMC) were mathematically calculated from PV, UPK, and moisture c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
8
1
Order By: Relevance
“…Popping. Popping is a process used traditionally for maize, sorghum, finger millet, and some pseudocereals (Parker and others 1999;Park and Maga 2002). It occurs when the grain is heated, producing an internal pressure build-up followed by a sudden pressure release.…”
Section: Role Of Cereal Cell Walls In Product Qualitymentioning
confidence: 99%
“…Popping. Popping is a process used traditionally for maize, sorghum, finger millet, and some pseudocereals (Parker and others 1999;Park and Maga 2002). It occurs when the grain is heated, producing an internal pressure build-up followed by a sudden pressure release.…”
Section: Role Of Cereal Cell Walls In Product Qualitymentioning
confidence: 99%
“…Thus, studies focused on physical traits have investigated kernel size and density (Cabral et al, 2016;Carpentieri-Pípolo et al, 2002;Park & Maga, 2002;Rangel et al, 2011;Song et al, 1991), percentage of unpopped kernels (Tian et al, 2001), flake size (Tian et al, 2001), and influence of pericarp thickness (Freire et al, 2020;Mohamed et al, 1993;Silva et al, 1993). In addition, studies related to the kernel chemical composition have determined the protein, starch, and oil contents, as, for example, those of Borras et al (2006) and Freire et al (2020).…”
Section: Introductionmentioning
confidence: 99%
“…Quality traits are critical to determine the basis for popping ability in popcorn. For example, starch and protein contents have been reported to greatly influence popping ability ( Brunson, 1937 ; Haugh et al , 1976 ; Robbins and Ashman, 1984 ; Da Silva et al , 1993 ; Park and Maga, 2002 ). Zhou et al (2016) analyzed the relationship between quality traits and popping ability by transferring the O2 gene into two popcorn inbred lines: they found that the o2 gene reduced the crude protein content and the expansion volume.…”
Section: Introductionmentioning
confidence: 99%